Clinical usefulness of left ventricular outflow tract velocity time integral for heart failure with reduced ejection fraction with rapid atrial fibrillation during landiolol treatment. Issue 1 (January 2022) - Iwahashi, Noriaki; Kirigaya, Jin; Abe, Takeru; Horii, Mutsuo; Takahashi, Hironori; Hanajima, Yohei; Kimura, Yuichiro; Minamimoto, Yugo; Okada, Kozo; Matsuzawa, Yasushi; Hibi, Kiyoshi; Kosuge, Masami; et al.
Highlights: l Echocardiography is a useful tool for the patients with acute heart failure. l Heart rate reduction in rapid atrial fibrillation by landiolol is a good option. l Left ventricular outflow tract velocity time integral (LVOT-VTI) can predict prognosis. l The absolute change in LVOT-VTI enables us to predict prognosis. Abstract: Background: Landiolol enables us to treat the patients with rapid atrial fibrillation (AF) with acute decompensated heart failure (ADHF) efficiently. We sought to determine the role of echocardiography in predicting the prognosis. Methods: Among 314 patients, a total 115 ADHF patients with reduced ejection fraction and rapid AF were enrolled. They received landiolol treatment to decrease the heart rate (HR) to <110 bpm and change HR (ΔHR) of >20% within 24 h. The dose of landiolol was increased every 2 h; then, we performed echocardiography repeatedly, at baseline, 2 h, and 24h. We followed the patients after discharge for 180 days, and checked cardiac death and HF hospitalization as major adverse cardiac events (MACE). Results: During initial hospitalization, 5 patients (4%) died. During 180 days after discharge, 19 (16%) out of 115 patients experienced MACE (2 cardiac death, 17 HF rehospitalization, 5 in-hospital death). Multivariate analysis showed that the change in left ventricular outflow tract-velocity time integral (LVOT-VTI) at 2 h was the most significant predictor for MACE (hazard ratio =1.21, 95% confidence interval: 1.10-1.83, p =0.0001). Kaplan-Meier curves demonstrated the patients with deteriorated LVOT-VTI at minimum dose landiolol suggested the high-risk patients for MACE (χ 2 =30.9, p <0.0001). Conclusions: During landiolol treatment, the patients with deteriorated LVOT-VTI predicted the poor prognosis. We may detect the high-risk patients by two-point echocardiography. UMIN000020084. Registered 1 November 2013 – prospective study https://upload.umin.ac.jp/cgi-open-bin/ctr/ctr.cgi?function=brows&action=brows&type=summary&language=J&recptno=R000023203 Graphic abstract: Image, graphical abstract